Market Risk Disclosure Practices of Banks: A Comparative Cross-country Analysis - Savvidou, Nicoletta (2009)
This dissertation is an empirical investigation of the disclosure practices of market risk of banks in four countries (UK, USA, Germany and Japan). It uses content analysis to produce qualitative and quantitative indicators of the degree of market risk disclosure to ascertain if differences exist between countries, as well as between banks within the same country. The study contributes to a research area that is under-researched, especially focusing on market risk of banks across countries.